Alpha-Calcitonin Gene Related Peptide: New Therapeutic Strategies for the Treatment and Prevention of Cardiovascular Disease and Migraine - Kumar, Ambrish; Williamson, Maelee; Hess, Andrew; DiPette, Donald J.; Potts, Jay D. (Frontiers in Physiology, 2022)
Alpha-calcitonin gene-related peptide (α-CGRP) is a vasodilator neuropeptide of calcitonin gene family. Pharmacological and gene knock-out studies have established a significant role of α-CGRP in normal and pathophysiological states, particularly in cardiovascular disease and migraines. α-CGRP knock-out mice with transverse aortic constriction (TAC)-induced pressure-overload heart failure have higher mortality rates and exhibit higher levels of cardiac fibrosis, inflammation, oxidative stress, and cell death compared to the wild-type TAC-mice. However, administration of α-CGRP, either in its native- or modified-form, improves cardiac function at the pathophysiological level, and significantly protects the heart from the adverse effects of heart failure and hypertension. Similar cardioprotective effects of the peptide were demonstrated in pressure-overload heart failure mice when α-CGRP was delivered using an alginate microcapsules-based drug delivery system. In contrast to cardiovascular disease, an elevated level of α-CGRP causes migraine-related headaches, thus the use of α-CGRP antagonists that block the interaction of the peptide to its receptor are beneficial in reducing chronic and episodic migraine headaches. Currently, several α-CGRP antagonists are being used as migraine treatments or in clinical trials for migraine pain management. Overall, agonists and antagonists of α-CGRP are clinically relevant to treat and prevent cardiovascular disease and migraine pain, respectively. This review focuses on the pharmacological and therapeutic significance of α-CGRP-agonists and -antagonists in various diseases, particularly in cardiac diseases and migraine pain.